Cognition in Parkinson's disease - Bašić, Jasna (Array, 2004)
Aim. Studies of accentuated drop in cognitive functioning in Parkinson's disease mostly use global intelligence measures that have a masking effect on differential drop in specific cognitive abilities. The main goal of this study was to investigate the possible differential drop in different cognitive tasks. Applied tests tapped fluid and crystallized intelligence, memory and metacognition. Method. A sample of 116 participants participated in the study. Half of the participants were diagnosed with Parkinson's disease (average duration of disease was 6.5± ; ; 5.68 years) and control group participants equaled them in age, sex and educational level. All participants were tested using Raven's Colored Progressive Matrices (CPM), Crichton Vocabulary Scale (CVS), memory subtests from Wechsler Adult Intelligence Scale (WAIS DS-F, WAIS DS-B), and Mini-mental Status Examination (MMSE). All participants were questioned concerning their metamemory and metacognition. In case of the clinical group 24 caregivers were asked about metamemory and metacognition of Parkinson’ s patients. Results. Parkinson's disease patients scored significantly lower than control group on CPM (F=18.14, p=0.001) and MMSE (F=4.04, p=0.047). Self-perceived speed of understanding was lower in Parkinson’ s patients (Mclinical=0.76± ; ; 0.43 ; Mcontrol=0.51± ; ; 0.51 ; F=6.57, p=0.012). Patients found their accuracy of metacognition to be more impaired than their caregivers did (Mpatient=0.83± ; ; 0.38 ; Mcaregiver=0.54± ; ; 0.51 ; t=2.29, p=0.035). Conclusion. The results point to a more pronounced cognitive damage of Parkinson's patients in fluid intelligence as opposed to crystallized intelligence. A brief investigation of metamemory and metacognition showed that patients with Parkinson's disease have a relatively accurate metamemory and metacognition.